2014
DOI: 10.7455/ijfs/3.1.2014.a2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Lactic Acid Fermentation on the Retention of Β-Carotene Content in Orange Fleshed Sweet Potatoes

Abstract: This study aimed to establish the effects of lactic fermentation on the levels of β-carotene in selected orange fleshed sweet potato (OFSP) varieties from Kenya. Furthermore,it sought to demonstrate fermentation as a potential process for making new products from sweet potato with enhanced nutraceutical attributes. The varieties (Zapallo, Nyathiodiewo and SPK004/06) were fermented with Lactobacillus plantarum MTCC 1407 at 25 ± 2ºC for 48 h and kept for 28 days to make lacto-pickles. During fermentation both an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
7
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 44 publications
3
7
1
1
Order By: Relevance
“…It seems that the NaCl addition had a positive effect on the β -carotene retention in green pickled tomatoes during the fermentation period. These findings are similar to Reference [ 33 ] for 10 vegetables and Reference [ 34 ] for orange fleshed sweet potato, which have reported the improvement of the levels of bioactive compounds and antioxidant capacities of pickled vegetables after 30 days of fermentation. Depending on the type of salt, this could help dissociate the carotenoid protein complexes into the brine or maintain them in the pickles.…”
Section: Resultssupporting
confidence: 92%
“…It seems that the NaCl addition had a positive effect on the β -carotene retention in green pickled tomatoes during the fermentation period. These findings are similar to Reference [ 33 ] for 10 vegetables and Reference [ 34 ] for orange fleshed sweet potato, which have reported the improvement of the levels of bioactive compounds and antioxidant capacities of pickled vegetables after 30 days of fermentation. Depending on the type of salt, this could help dissociate the carotenoid protein complexes into the brine or maintain them in the pickles.…”
Section: Resultssupporting
confidence: 92%
“…The fermentation of seeds for 48 h resulted in the highest total carotenoid content of 14.0 mg/g compared to 6.5 mg/g for unfermented "Nabag" seeds. This finding agrees with that of Oloo et al [39], who reported a significant increase in the carotenoid content of orange flash potato fermented for 2 days. Similarly, Ortiz et al [40] observed that the fermentation of bio-fortified maize for 24 and 72 h resulted in a 100% increase of pro-vitamin A carotenoid, while prolonging the fermentation time to 120 h or more reduced the carotenoid content of maize.…”
Section: Effect Of Naturalsupporting
confidence: 93%
“…Fermentation can increase the release of carotenoids [ 55 ]. For example, lactic acid fermentation can preserve β-carotene more than other processing techniques, such as deep-frying, blanching, and drying [ 56 ]. In addition, Lactobacillus plantarum (29DAN, 83DAN) was able to increase the carotenoid content in wheat dough due to the higher solubility of these antioxidant compounds [ 50 ].…”
Section: Changes Of Antioxidant Constituents In Plant-based Food Materials During Fermentationmentioning
confidence: 99%